Evaluation of Concatenation Planning of Crushing Plant Production System Using Analytic Hierarchy Process (AHP) Method at PT Buana Eltra Coal Processing Unit, South Sumatra - Endarto Endarto; Restu Juniah; Weny Herlina (Indonesian Journal of Environmental Management and Sustainability, 2018)
Coal processing activity conducted at the Coal Processing Unit (Stockpile) Martapura PT. Buana Eltra aims to reduce the size of coal to a smaller size in accordance with market demand of 5-10 cm. Processing is done with a combination of crushing plant and excavator called concatenation of production system. Concatentation of the current production system is a concatenation between Komatsu PC300 excavator and 10 cm roll crusher dimension which produces 145,6701 tons/hour and takes 20,59 hours and is considered inefficient and ineffective to reach production target of 3000 tons/day. Based on the above, it is necessary to evaluate the concatenation of crushing plant production system so that the processing process will be optimally. The method used in this concatenation evaluation is the Analytic Hierarchy Process (AHP) method. The alternative is the concatenation between, Komatsu PC200 excavator - 10 cm roll crusher dimension, Komatsu PC200 excavator - 5 cm roll crusher dimension and Komatsu PC300 excavator - 5 cm roll crusher dimension. The selection of these alternatives is based on qualitative data (criteria from experts) and quantitative data so as to produce optimal choice. Based on the evaluation and analysis of the two types of data then selected concatenation excavator Komatsu PC200 - dimension roll crusher 10 cm which has a productivity of 207,8468 tons/hour and the time required to reach 300 tons/day for 14.43 hours.